Pengaruh Edukasi Media Booklet Terhadap Pengetahuan Orang Tua Tentang Pencegahan Pneumonia Pada Balita di Kelurahan Mahawu Kota Manado - Petronela Mamentu; Rukmini Harun (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
One of the main causes of infant death in Indonesia is pneumonia. The number of cases affects the increasing incidence of pneumonia in toddlers, from factors such as the aspects of the child himself, environmental factors, and parents (mothers). The lack of parental knowledge in the form of education is one of the risks of increasing pneumonia in toddlers. The purpose of this research was to find out the effect of media booklet education on parents' knowledge about pneumonia prevention in toddlers in Mahawu Village, Manado City. The research using a pre-experimental methods, with One Group Pre-test and Post-test design. The sample was taken in 20 respondents using purposive sampling. The research instrument used is a questionnaire sheet. The data obtained were analyzed using the McNemar test with a meaningfulness level (?= 0.05).From the Mc Nemar test, it was obtained of P Value = 0.001 with a significance <0.05, which means Ha is accepted and Ho is rejected. The conclusion in this research is that there is an effect of media booklet education on parents' knowledge about pneumonia prevention in toddlers in Mahawu Village, Manado City. It is expected that the result of this research can increase parent’s knowledge about the prevention of pneumonia in toddlers.